APPLICATION OF BEHAVIORAL ARCHITECTURE IN A HALFWAY HOUSE AND COACHING CENTER FOR STREET CHILDREN IN MEDAN - Suwantoro, Hajar; Tumanggor , Cindy Thalia Bernadet (Komunitas Menulis dan Meneliti (Kolibi), 2024)
The significant population of street children in Medan City underscores pressing child welfare issues, predominantly driven by economic factors. In response, this study examines the application of behavioural architecture in designing halfway houses and coaching center for street children in Medan. The concept of behavioural architecture seeks to create environments that align with street children's unique behaviours and needs, ensuring both physical and psychological comfort through strategic architectural design, interior spaces, outdoor areas, and circulation plans. This research employs qualitative methods, including data collection through observation, and literature reviews. The findings reveal that incorporating behavioural architecture principles into these facilities' design can significantly enhance street children's living and developmental conditions, providing them with a supportive and nurturing environment.